2017
DOI: 10.1155/2017/1262650
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Analysis of Multilayers Based MEMS Resonators

Abstract: The dynamic behavior of a microelectromechanical system (MEMS) parallel and electrically coupled double-layers (microbeams) based resonator is investigated. Two numerical methods were used to solve the dynamical problem: the reduced-order modeling (ROM) and the perturbation method. The ROM was derived using the so-called Galerkin expansion with considering the linear undamped mode shapes of straight beam as the basis functions. The perturbation method was generated using the method of multiple scales by direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Perturbation methods are applied to obtain the modulation equations that govern the amplitude and phase response of the resonator. Examples of these studies can be found in microbeams [107,166,217,[261][262][263][264][265][266][267][268][269][270][271][272][273][274][275][276][277][278][279], torsional mirrors [280,281], self-excited resonators [282][283][284][285], PZT based MEMS models [286][287][288], MEMS filters [171], MEMS arch resonators [169,289], carbon Nanotubes [290], and coupled oscillators [291]. The influence of secondary-resonance excitations on MEMS has been also studied.…”
Section: Nonlinear Response Of Mems Resonators Using Perturbation Methodsmentioning
confidence: 99%
“…Perturbation methods are applied to obtain the modulation equations that govern the amplitude and phase response of the resonator. Examples of these studies can be found in microbeams [107,166,217,[261][262][263][264][265][266][267][268][269][270][271][272][273][274][275][276][277][278][279], torsional mirrors [280,281], self-excited resonators [282][283][284][285], PZT based MEMS models [286][287][288], MEMS filters [171], MEMS arch resonators [169,289], carbon Nanotubes [290], and coupled oscillators [291]. The influence of secondary-resonance excitations on MEMS has been also studied.…”
Section: Nonlinear Response Of Mems Resonators Using Perturbation Methodsmentioning
confidence: 99%
“…An excellent match is noticed between the MTS solution and the numerical solution of the truncated Eq. (31). The frequency response curves of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To understand the nonlinear dynamical behavior of MEMS/NEMS resonators, it is important to develop analytical models that predict the resonator's behavior under different excitation conditions. Commonly, to treat the complex parallel-plate electrostatic forcing term in the equation of motion, the forcing term is expanded in Taylor series, where some significant terms are retained and higher-order terms are dropped [19,21,24,[31][32][33][34]. This is done in order to obtain a simpler equation to carry out further analysis such as bifurcation studies, stability analysis, and analytical solutions using perturbation techniques.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development and extensive application of micro-/nano-technology [3], the material micro-deformation is also common in micro-structures and even nano-structures and devices because of the complexity of external loadings in such as micro-/nano-electromechanical systems, micro-switches, micro-resonators, micro-sensors, and microoscillators [4][5][6][7][8]. For beams with a macroscopic length, the classical mechanics of materials and elasticity theory are enough to characterize and explain the mechanical behaviors [9,10].…”
Section: Introductionmentioning
confidence: 99%